Barriers to sealant guideline implementation within a multi-site managed care dental practice - Deborah E. Polk; Robert J. Weyant; Nilesh H. Shah; Jeffrey L. Fellows; Daniel J. Pihlstrom; Julie Frantsve-Hawley (BMC, 2018)
Abstract Background The purpose of this study was to identify barriers frequently endorsed by dentists in a large, multi-site dental practice to implementing the American Dental Association's recommendation for sealing noncavitated occlusal carious lesions as established in their 2016 pit-and-fissure sealant clinical practice guideline. Although previous research has identified barriers to using sealants perceived by dentists in private practice, barriers frequently endorsed by dentists in large, multi-site dental practices have yet to be identified. Identifying barriers for these dentists is important, because it is expected that in the future, the multi-site group practice configuration will comprise more dental practices. Methods We anonymously surveyed the 110 general and pediatric dentists at a multi-site dental practice in the U.S. The survey assessed potential barriers in three domains: practice environment, prevailing opinion, and knowledge and attitudes. Results were summarized using descriptive statistics. Results The response rate to the survey was 62%. The principal barrier characterizing the practice environment was concern regarding liability; endorsed by 33% of the dentists. Many barriers of prevailing opinion were frequently endorsed. These included misunderstanding the standard of practice (59%), being unaware of the expectations of opinion leaders (56%) including being unaware of the guideline itself (67%), and being unaware of what is currently being taught in dental schools (58%). Finally, barriers of knowledge and attitudes were frequently endorsed. These included having suboptimal skill in applying sealants (23% - 47%) and lacking knowledge regarding the relative efficacy of the different ways to manage noncavitated occlusal carious lesions (50%). Conclusions We identified barriers frequently endorsed by dentists in a large, multi-site dental practice relating to the practice environment, prevailing opinion, and knowledge and attitudes. All the barriers we identified have the potential to be addressed by implementation strategies. Future studies should devise and test implementation strategies to target these barriers.